Pengaruh Media Colour Corrugated Paper (Kokoru) Terhadap Kemampuan Kreativitas Anak Usia Dini - Tiara Julianti; Akbari; Alrefi; Rini Susanti (Institut Agama Islam Negeri Madura, 2024)
This research aims to determine the effect of colored corrugated paper (kokoru) media on the creative abilities of group B children at KB Aisyiyah 5 Baturaja. The type of research used was pre-experiment with a one-shot case study design. The sampling technique used purposive sampling, namely class B with a total of 20 children consisting of 12 boys and 8 girls. The data collection technique used will then be analyzed using a one-sample t-test. The results obtained were t-value of 5.74 with a significance of 0.05 and the degrees of freedom were 19 so that a t-table of 1.729 was obtained. So the t-value of 5.74 is greater than t-table of 1.729. So it can be concluded that there is an influence of Color Corrugated Paper (Kokoru) Media on the Creativity Abilities of Group B Children at KB Aisyiyah 5 Baturaja.